EFFICACY AND SAFETY OF SEMI-RIGID URETEROSCOPY, FLEXIBLE URETEROSCOPY, AND SHOCK WAVE LITHOTRIPSY FOR INITIAL TREATMENT OF PROXIMAL URETERAL STONES- A COMPARATIVE STUDY - ADNAN, M; AHMAD, I; KHAN, MAH; SAIFULLAH; HUSSAIN, M; JAVED, N (Biological and Clinical Sciences Research Journal, 2023)
This study was designed to compare the efficacy and safety of semi-rigid ureteroscopy, shock wave lithotripsy and flexible ureteroscopy for treating proximal ureteral stones. A retrospective study was conducted in the Urology Department of Bakhtawar Amin Trust Hospital, Mukhtar A. Sheikh Hospital Multan & Lahore from 06th Sep 2021 to 06th Sep 2022. A total of 100 patients with 11-20mm proximal ureteral stones were included in the study. The patients underwent one of the three procedures; semi-rigid ureteroscopy (23 patients), shock wave lithotripsy (35 patients) and flexible ureteroscopy (42 patients) and their results were compared. The study was conducted on a total of 100 patients. The hospital stay and operation time duration in the SWL group was shorter than in the URS groups (p < 0.001). F-URS had a higher success rate than SWL or sr-URS (p < .001), and that of sr-URS was higher as compared to SWL (p<.001). The furs group had the highest efficiency quotient. Complication grading based on the modified Clavien classification system does not show significant differences. f- URS had a lesser need for the auxiliary procedure, shorter hospital stays, and longer operation duration than sr-URS. F-URS is an effective lithotripsy procedure in treating 11-20mm proximal ureteral stones with fewer complications and retreatment requirements than SWL and sr-URS.